A mechanism of sialylation functionally silences the hyaluronan receptor LYVE-1 in lymphatic endothelium. - Nightingale, T; Frayne, M; Clasper, S; Banerji, S; Jackson, D (2009)
The major lymphatic endothelial hyaluronan receptor LYVE-1, a Link superfamily glycoprotein similar to the hyaluronan-binding/inflammatory leukocyte homing receptor CD44, was initially implicated in hyaluronan (HA)-mediated cell adhesion and lymph-borne hyaluronan metabolism. However, the apparently normal phenotype of Lyve-1 knock-out mice and the recent demonstration that the receptor undergoes cytokine-induced endocytosis independent of HA uptake have cast doubt on such functions. Here we present new data that reconcile these anomalies by showing that LYVE-1 is functionally "silenced" in a cell-specific fashion by autoinhibitory glycosylation. We demonstrate that LYVE-1 transfected in HEK 293T fibroblasts and Jurkat T cells is competent to bind HA, whereas the endogenous receptor in cultured lymphatic endothelial cells or the receptor transfected in Chinese hamster ovary and HeLa cells is not. Moreover, through a combination of mutagenesis and functional analysis in HEK 293T fibroblasts and glycosylation-defective Chinese hamster ovary cell lines, we reveal that the inhibitory mechanism is reversible and is exerted by terminal sialylation, most likely through alpha2-3 or alpha2-6 linkage to O-glycans. Finally, we provide evidence that the mechanism operates in vivo by showing that native LYVE-1 in primary lymphatic endothelial cells is extensively sialylated and that HA binding can be reactivated by neuraminidase treatment of the soluble ectodomain. These results reveal unexpected complexity in the regulation of LYVE-1 function and raise the possibility that this receptor, like CD44, may become active after appropriate unmasking in vivo.